Differential Talin cleavage in transformed and non-transformed cells and its consequences - Hu, Xian; Jalal, Salma; Yao, Mingxi; Bakke, Oddmund; Margadant, Felix; Sheetz, Michael (Frontiers in Cell and Developmental Biology, 2024)
This study investigates differences in focal adhesion (FA) morphology and Talin cleavage levels between transformed and non-transformed cell lines. Utilizing fluorescently tagged wild-type Talin and Talin mutants with calpain cleavage site mutations, FA structures were visualized. Mutations in different Talin cleavage sites showed varying impacts on FA morphology and distribution across melanoma cell lines (Meljuso, A375P, A2058) and a non-transformed cell line (HFF). Western blot analysis, ratiometric fluorescence intensity-based measurements, and FRAP experiments revealed higher Talin cleavage levels within FAs of transformed cell lines compared to non-transformed cells. Additionally, growth assays indicated that reducing calpain cleavage levels attenuated transformed cell growth. These findings suggest that Talin cleavage level is crucial for FA morphology and assembly, with higher levels observed in transformed cells, influencing their growth dynamics.